Case Report: Labor induced coccydynia associated with Modic I changes successfully treated with platelet-rich plasma - Vuković, Miloš; Nosek, Igor; Vuković, Jelena; Ilić, Đorđe; Kozić, Duško; Boban, Jasmina (Frontiers in Immunology, 2023)
Imaging can aid in determining potential causes of coccygeal pain and therefore guide clinicians to carry out individualized treatment. We represent a case of postpartum coccydynia treated by platelet-rich plasma (PRP) which was assessed and followed by MRI. A primipara with uncomplicated labor developed coccygeal pain after delivery that significantly limited her postpartum recovery. On the first MR scan, recorded 6 months after delivery, there were edematous changes of the vertebral endplates of Co1-4 level (Modic type I) with the presence of pronounced precoccygeal venous drainage. Degenerative changes with signs of edema in the area of the pubic symphysis were recorded. The sacroiliac joints had regular morphological features. Since the patient was breastfeeding, PRP therapy was applied with a total of three injections in the area of the coccyx subcutaneously, once every 3 months. The subjective feeling of pain reduction after each injection was about 30%, with the complete withdrawal of pain after one year and still pain-free at the two-year follow-up. One year after the initial MR imaging, a follow-up MR examination was performed, where almost complete resolution of edematous changes in the previously present zones was observed, with residual minor edema of the vertebral endplates at the Co2-3 level. Edema of the pubic bones in the area of the pubic symphysis also subsided. A case of labor-induced coccydynia that was represented as Modic type I changes without neither fracture or luxation was successfully treated with PRP with complete resolution of symptoms.